Electoral system in Malaysia: the need for a representative Government / Nicholas Bowie Buyong, Mohd. Nizam Yahya and Freddy Bunyak - Buyong, Nicholas Bowie; Yahya, Mohd. Nizam; Bunyak, Freddy (Faculty of Law, 2012)
The gist of democratic election is to create a government that represents the voice of the people. This research was carried out to study the Malaysian electoral system and to identify whether our election system is in compliance with the gist of the democratic election that allows the establishment of a representative government and to identify the deficiencies in our system. To improve the deficiencies it is necessary to perform a comparative analysis of the different types of electoral systems practice in most part of the world and its implementation in some chosen countries in this research such as France, German, United Kingdom and South Africa. The comparative study is vital so as to see the strength and weaknesses of the other systems adopted in countries under research. From the comparative analysis the research proposed some recommendations to improve the deficiencies present in our electoral system. The result of this study may be useful as reference in improving our electoral system so that it is more democratic and accountable to the people, rather than focusing on winning the election which is not the pure purpose of having an election.